Islamization of knowledge in the curriculum among academics at the International Islamic University Malaysia: a structural equation modeling (SEM) approach - Ismail, Nik Ahmad Hisham; Teke, Mustafa; Idrus, Faizah (The International Islamic University Malaysia, 2017)
Islamization of Knowledge (IOK) is documented in the vision and mission of the International Islamic University Malaysia (IIUM) which impetuses its implementation in many aspects of the IIUM academic and non academic programmes. The main objective of this study is to examine the importance of the IOK particularly in addressing the strategies and practices among the academics to integrate the IOK in the curriculum. There are seven components of the implementation of the IOK at the IIUM. The components include Belief, Content, Teaching and Learning Process,Evaluation/Assessment, Purpose, Product, and Student Improvement (Value). This paper aims to further investigate or evaluate the implementation of the IOK through identifying the relationships among these components as perceived by IIUM academics. A 65-item self-reported questionnaire was developed to collect the data on the IOK from 306 academics. The Statistical Package for Social Science (SPSS) Version 15 was used to compute the descriptive statistics.Analysis of a Moment Structures (AMOS) version 16.0 was used to perform Confirmatory Factor Analysis (CFA) and full-fledged Structural Equation Model (SEM). The hypothesized model of the IOK among the academics was tested using Structural Equation Modeling (SEM). The results have shown a good model fit (RMSEA=0.058; cfi=.948; and tli=0.942). However, Belief in the IOK as a component was not a significant predictor of two curriculum dimensions namely pedagogy and evaluation (C.R.>1.96). This indicates that recognizing the importance of the IOK is not sufficient in both adopting evaluation methods and selecting appropriate pedagogical approaches among academics.However, when the academics believed in the importance of the IOK,they sought for further training and knowledge from the experts.Thus, the relationship between Belief in the IOK and training and knowledge collectively impact the academics’ evaluation in the classroom. Furthermore, there was a significant relationship between pedagogical approaches and selected products of the IOK. There was an indication that lecturers who adopted the IOK in their pedagogy approaches had the tendency to produce items of the IOK such as articles, chapter of a book, a book, proceeding and thesis.The study suggested that future study to emphasis on accomplishment of the IOK.